2016
DOI: 10.1016/j.jacc.2016.03.477
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Adults With Congenital Heart Disease in 15 Countries

Abstract: This large-scale, international study found that overall QOL in adults with CHD was generally good. Variation in QOL was related to patient characteristics but not country-specific characteristics. Hence, patients at risk for poorer QOL can be identified using uniform criteria. General principles for designing interventions to improve QOL can be developed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
138
4
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(165 citation statements)
references
References 28 publications
15
138
4
6
Order By: Relevance
“…414 Higher education, employment, independent living, and being married have been associated with better quality of life among adults with CHD. 432,433 As a group, however, adults with CHD, particularly those with more complex forms, tend to have lower educational attainment and higher rates of unemployment. [434][435][436] Furthermore, there may be specific challenges associated with romantic relationships, sexuality, and family planning.…”
Section: Psychosocial Prevalencementioning
confidence: 99%
“…414 Higher education, employment, independent living, and being married have been associated with better quality of life among adults with CHD. 432,433 As a group, however, adults with CHD, particularly those with more complex forms, tend to have lower educational attainment and higher rates of unemployment. [434][435][436] Furthermore, there may be specific challenges associated with romantic relationships, sexuality, and family planning.…”
Section: Psychosocial Prevalencementioning
confidence: 99%
“…In the present study, Maltese ACHD patients also reported good QOL as measured by LAS and SWLS and this was not significantly different from that of patients from other European countries. Indeed, Maltese participants had the fourth best QOL overall among all participating countries in the main APPROACH-IS study [7]. As per the second study aim, the presence of mood, anxiety or other psychiatric disorders was revealed to be the only medical factor to predict a poorer QOL as assessed by either scale among Maltese ACHD patients.…”
Section: Discussionmentioning
confidence: 89%
“…The present study utilises data from the large multi-centre collaboration "Assessment of Patterns of Patient-Reported Outcomes in Adults with Congenital Heart disease -International Study" (APPROACH-IS) [6,7] in which Malta was a participating centre, in order to gain further insight into QOL among Maltese ACHD patients. The aims were: (a) to compare QOL in Maltese ACHD patients with ACHD patients in other participating European countries, and (b) to investigate the role of several medical factors as predictors of QOL among Maltese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with low QoL were older age, lack of employment or disability, no history of marriage and poor NYHA class. Country-specific characteristics influencing QoL were not observed (1).…”
mentioning
confidence: 94%
“…Recently Apers et al published data from the APPROACH-IS (Assessment of Patterns of PatientReported Outcomes in Adults with Congenital Heart Disease-International Study) consortium including a cohort of 4028 adults with congenital heart disease from 15 different countries (1). The aim of the study was to evaluate whether country specific characteristics may have an impact on quality of life.…”
mentioning
confidence: 99%